Sustainable 3D Concrete Printing for Eco-conscious Construction: Recycled Aggregates and Low-carbon Binders - Colyn, Markus Leon (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.